KUASA MENJUAL NOTARIIL SEBAGAI INSTRUMEN PEMENUHAN KEWAJIBAN DEBITUR YANG WANPRESTASI DALAM PERJANJIAN UTANG PIUTANG - Dicka Prasminda, Gede; Usfunan, Yohanes; Udiana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 1 (2017)DO - 10.24843/AC.2017.v02.i01.p05, 2017)
The granting of power of attorney to sell the land rights as an instrument for the fulfillment of the obligations of the debtor in a loan agreement of a notarial deed may commonly be found in the everyday practice of the notaries. Power of Attorney to sell is used by the proxy to sell the land of the authorizer in the event that the authorizer (debtor) experienced defaults. T he Civil Law Code and the Law No. 4 of 1996 on Mortgage do not stipulate the power attorney to sell as an instrument in the loan agreement . There are two legal content s analyzed from the vacancy of norms regarding the power of attorney to sell, namely: (1) how the arrangement of power of attorney to sell of the land  rights as an instrument for the fulfillment of obligations on the loan agreement in the legislation on the guarantee law and (2) the legal effect of power of attorney to sell the land rights as an instrument for the fulfillment of obligations of the debtor in case of default under the loan agreements in connection with the execution of the law of guarantee. The type of research used in this thesis is a normative legal research with the statutory, concept and case approaches. Based on the research results, it was revealed that the power of attorney to sell is based on the agreement of the parties which make the basis of the principle of freedom of contract. The Power of Attorney Deed shall be valid unless otherwise it is canceled by the judge with a court ruling that has the binding legal force. The use the deed of power of attorney to sell is considered weak because the power of attorney to sell can not be used as a basis for executing security object between the grantor and the recipient of the power of attorney . Deed of power of attorney to sell is deemed not obtain legal certainty because at the time of registration of  transfer of land rights, the power of attorney to sell can not be accepted by the local Land Registry Office. Responsibility for the grantor and the recipient of power of attorney  is related to the obligations and rights of the grantor and the recipient of the power of attorney. As for the responsibility of the notary who made the deed of power of attorney to sell can be studied from three aspects, namely: (1). Civil responsibility; (2). Administrative responsibility; and (3). Criminal responsibility. Legal remedies that can be taken if the debtor is experiencing defaults can be done by way of a summons in advance without selling the rights of the land owned by the grantor of the power of attorney to sell (the debitor).